PENGARUH PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SMK YADIKA NATAR - Fitria, Nur (LPPM STKIP PGRI Bandar Lampung, 2019)
This research uses experimental method that is by using method of learning cycle. From hypothesis testing using t test statistic formula to know whether there is influence of aplication of learning method learning cycle. After testing of hypothesis on test of different of two mean and calculationof data of economic learning result by using statistic formula, hence in can t hit 4,30 and t tab 2,00 at 5% significant level so that proved that t hit > t tab. With so it can be concluded “there is influence of learning method of learning cycle to students economic learning result of class X SMK Yadika Nataryear lesson 2018/2019. Judging from teh mean score of the students, the experimental class 83,37 and the control class had a average value of x = 71, 03. So the average students economic learning outcomes using learning cycle method are higher than students using conventional learning methods